Coal fired power plant instrument - Anuar, Asyran; Aini, Syahmi Afiq Aqmal; Muhammad Basri, Mohd Qamarul Arifin; Abdul Rahim, Ruzairi (Penerbit UTHM, 2017)
Coal fired is one of the most valuable sources that can be used to sustain the existence of life. Coal fired can be exploited in producing electricity. In Malaysia, there a few power plants that use coal fired as main source. To name a few, in Manjung there are coal fired plant produced 3100MW, in Tanjung Bin produced 2100MW and Jimah Power produced 1400MW. All these power plants located in South East Malaysia that used coal fired as main source. There are a lot of instrument specifically sensors and transducers applied in power plant. All these sensors and transducers used to monitor every single thing such as pressure, temperature, level and many other measurement parameters. The sensors and transducers that involved in monitoring the measurement parameters are pressure gauge, pressure transmitter, thermocouple, flow transmitter, proximity sensor, limit switch, radar, RTD and many more. Power plant applied process control system in order to link up the instruments and Human Machine Interface (HMI). HMI is a software application that presents information to an operator or user about the state of a process, and to accept and implement the operators control instructions. Typically information is displayed in a graphic format (Graphical User Interface or GUI) [1]. In general coal fired power plant or known as thermal power station is a power plant in which the prime mover steam driven. Water is heated to produce steam which drives the turbine as a result induced an electrical energy.